Factor structure of the Malay-version Generalized Anxiety Disorder-7 (GAD-7) questionnaire among patients with diabetes mellitus - Woon, Luke Sy-Cherng; Hatta Sidi,; Norlaila M, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
The Malay-version Generalised Anxiety Disorder-7 (GAD-7) questionnaire previously demonstrated good concurrent validity, i.e. sensitivity and specificity as a screening instrument for anxiety. However, its psychometric properties on factorial validity had not been further investigated. This study investigated the factor structure of the Malay-version GAD-7 in among 300 diabetic outpatients (mean age: 60.4 years, SD: 13.4 years; 52.7% male) in a Malaysian university hospital in Kuala Lumpur. Study participants completed questionnaires on sociodemographic information, the GAD-7, the Beck’s Depression Inventory (BDI), and the WHOQOL-BREF instrument. The Malay-version GAD-7 displayed good internal consistency (Cronbach’s α=0.91) and satisfactory convergent validity with depression (Pearson’s R=0.642, p<0.001), overall perceptions of QOL (R=-0.277, p<0.001) and health (R=-0.257, p<0.001). In exploratory factor analysis, there was only one component with an eigenvalue >1 (eigenvalue=4.614), suggesting a unidimensional factor structure. All seven items were loaded on a higher-order factor (‘generalized anxiety’) in confirmatory factor analysis. This model did not have a good fit with the data. After examining the modification indices, the model was respecified to allow covariance of the error terms of items 1 and 2, and 2 and 3. The respecified model appeared to fit the data better (χ2=35.216, df=12, p<0.001, CFI=0.98, TLI=0.97, RMSEA=0.08, and AIC=67.22). The findings suggested that items 1, 2 and 3 of GAD-7 may share distinctive variance out of that explained by the ‘generalized anxiety’ factor. Overall, the Malay-version GAD-7 appeared to be a valid measurement of the symptoms of anxiety in this study.